2013
DOI: 10.1042/bsr20130043
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the cytochrome cd1 nitrite reductase NirS from Pseudomonas aeruginosa requires transient interactions between the three proteins NirS, NirN and NirF

Abstract: The periplasmic cytochrome cd1 nitrite reductase NirS occurring in denitrifying bacteria such as the human pathogen Pseudomonas aeruginosa contains the essential tetrapyrrole cofactors haem c and haem d1. Whereas the haem c is incorporated into NirS by the cytochrome c maturation system I, nothing is known about the insertion of the haem d1 into NirS. Here, we show by co-immunoprecipitation that NirS interacts with the potential haem d1 insertion protein NirN in vivo. This NirS–NirN interaction is dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 37 publications
5
46
0
Order By: Relevance
“…For the final insertion of heme d 1 into NirS, the system uses NirN, a structural homologue of NirS without nitrite reductase activity. NirS, NirF, and NirN form a stable complex during nitrite reductase maturation (26). In agreement, protein interactions of NorB and NorC with NirN were detected in our study (Table 3).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…For the final insertion of heme d 1 into NirS, the system uses NirN, a structural homologue of NirS without nitrite reductase activity. NirS, NirF, and NirN form a stable complex during nitrite reductase maturation (26). In agreement, protein interactions of NorB and NorC with NirN were detected in our study (Table 3).…”
Section: Resultssupporting
confidence: 79%
“…The strongest interaction of NorBC (bait) for an isolated prey protein was detected for the periplasmic, membrane-attached lipoprotein NirF, the last enzyme in heme d 1 synthesis and a cofactor of nitrite reductases (26). For the final insertion of heme d 1 into NirS, the system uses NirN, a structural homologue of NirS without nitrite reductase activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this proposal it has been shown that NirN from P. aeruginosa interacts with both NirS and NirF in vivo. However, in that study it was also observed by UV-visible absorption spectroscopy of periplasmic protein fractions that the cofactor content of NirS in the P. aeruginosa ⌬nirN strain was different from that in the P. aeruginosa WT strain (15). Later, the same observation was reported for a ⌬nirN strain of Magnetospirillum gryphiswaldense (17).…”
mentioning
confidence: 55%
“…Depending on the organism, NirF is either a soluble periplasmic protein or attached to the outer face of the cytoplasmic membrane, most likely by a lipid anchor (14,15). In addition to its periplasmic location, purified recombinant NirF from Paracoccus pantotrophus has been shown to bind heme d 1 in vitro (13).…”
mentioning
confidence: 99%